2016
DOI: 10.1002/hbm.23330
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of brain connectivity in primary open angle glaucoma

Abstract: Our aim was to assess in primary open angle glaucoma (POAG), a major cause of irreversible blindness worldwide, whether diffuse brain changes recently shown in advanced stage can be detected since the early stage. We used multimodal magnetic resonance imaging (MRI) in 57 patients with the three POAG stages and in 29 age-matched normal controls (NC). Voxelwise statistics was performed with nonparametric permutation testing. Compared with NC, disrupted anatomical connectivity (AC) was found in the whole POAG gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
91
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 68 publications
(115 reference statements)
6
91
0
8
Order By: Relevance
“…Finally, functional MRI may offer new insights into the brain modifications associated with glaucoma, as suggested by two recent studies, showing functional modifications of the visual cortex at the earliest stages of the disease. 47,48 In conclusion, we confirmed microstructural changes of optic radiations in glaucoma and its association with glaucoma severity. In accordance with several other studies, DTI appears as an objective measurement for evaluating alterations of the visual pathways in glaucoma and provides new insight in the pathophysiological process of glaucoma.…”
Section: Optic Radiations Microstructural Changes In Glaucomasupporting
confidence: 79%
“…Finally, functional MRI may offer new insights into the brain modifications associated with glaucoma, as suggested by two recent studies, showing functional modifications of the visual cortex at the earliest stages of the disease. 47,48 In conclusion, we confirmed microstructural changes of optic radiations in glaucoma and its association with glaucoma severity. In accordance with several other studies, DTI appears as an objective measurement for evaluating alterations of the visual pathways in glaucoma and provides new insight in the pathophysiological process of glaucoma.…”
Section: Optic Radiations Microstructural Changes In Glaucomasupporting
confidence: 79%
“…In fact, NTG cases represent about 25–32% of overall POAG cases, both in the Beaver Dam study in Wisconsin, USA [Klein et al, ] and in the Egna Neumarkt study in Alto Adige, Italy [Bonomi et al, ] whereas NTG prevalence is three to four times higher than HTG in Japan [Shiose et al, ]. In POAG with raised IOP, we and others have previously demonstrated through multimodal brain MRI widespread damage of diffusion tensor imaging (DTI)‐derived anatomical connectivity (AC), gray matter (GM) atrophy and/or altered resting state functional connectivity (FC) that can go beyond the visual system, even since the early disease stage [Dai et al, ; Frezzotti et al, ; Jiang et al, ; Wang et al, ; Zikou et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent multimodal, cerebral MRI and diffusion tensor imaging studies have shown diffuse structural and functional changes in the brains of patients with different stages of glaucoma. 10,11 These changes affected visual and nonvisual structures in the brain. Beyond atrophy of the visual cortex, these studies disclosed atrophy of scattered, distant gray matter regions such as the frontoparietal cortex, hippocampi, and cerebellar cortex, and decreased functional connectivity in visual, working memory and dorsal attention networks.…”
mentioning
confidence: 99%
“…The same study in glaucoma disclosed altered integrity of the superior longitudinal fascicle, resulting in decreased fractional anisotropy. 11 This fascicle is involved in providing information regarding perception of visual space to the prefrontal cortex, which in turn is responsible for the planning phase of an antisaccade. 52 Furthermore, the white matter of the precuneus showed abnormalities even in earlystage POAG.…”
mentioning
confidence: 99%
See 1 more Smart Citation